Atividade antioxidante, caracterização química e botânica de mel amargo proveniente do Município do Cantá-RR - Maciel, Iolete do Nascimento Araújo (2013)
The bitter honey production in the city of Cantá-RR has been attribute by beekeepers in the region to the period of flowering plants of the genus Vochysia. This research aims to investigate the existence of chemical markers that can confirm the botanical origin of the honey, as well as verify their chemical composition and antioxidant activity. Thus, we prepared extracts of bitter honey by XAD-2, C18, liquid-liquid (dichloromethane) and lyophilized honey. For comparison of the constitution were also obtained the extracts ethanol of the flowers without anthers and of the anthers of the flowers, rich in pollen. The extracts of honey XAD-2 and ethanol flowers were fractionated, obtaining extracts with hexane, chloroform, ethyl acetate and methanol. Mass spectrometric analyzes were performed with the different extracts and there was a great similarity between the spectra. By using authentic standards, chrysin and caffeic acid were identified in the extracts of bitter honey. In hexanic extract analyzes, through gas chromatography coupled to mass spectrometry (GC-MS), several n-alkanes and n- alkenes were identified with times of retention and identical retention index in the honey and in the flowers. To determine the position of the double bond, a derivatization with dimethuldisulfide was performed. The similar n-alkenes in extracts of honey and flowers presented unsaturation at position 1. Spectrophotometric analyses were performed to quantify the phenolic compounds getting to result of 94,64 mg of gallic acid /100 g of honey and flavonoids with 86,23 g/100g honey. The honey presented a white coloration, based on the Pfund scale and antioxidant activity one IC50 of 16,94 mg / mL,determined by means of the DPPH method. This work confirmed the botanical origin of honey obtained by melissopalynology and chemical data, and also contributed to the chemical characterization of the honey through quantification of some classes of natural products and their antioxidant activity.